2010
DOI: 10.1371/journal.pcbi.1000743
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Co-Receptor Usage of HIV-1 from Genotype

Abstract: Human Immunodeficiency Virus 1 uses for entry into host cells a receptor (CD4) and one of two co-receptors (CCR5 or CXCR4). Recently, a new class of antiretroviral drugs has entered clinical practice that specifically bind to the co-receptor CCR5, and thus inhibit virus entry. Accurate prediction of the co-receptor used by the virus in the patient is important as it allows for personalized selection of effective drugs and prognosis of disease progression. We have investigated whether it is possible to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 40 publications
3
99
0
Order By: Relevance
“…The type of co-receptor is crucial for the aggressiveness of the virus and the available treatment options. Hence, Dybowski et al [16] proposed to predict co-receptor usage based on the viral genome sequences. A random forest based method is developed to predict co-receptor usage for new sequences using structures and sequences of "gp120".…”
Section: Biological Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The type of co-receptor is crucial for the aggressiveness of the virus and the available treatment options. Hence, Dybowski et al [16] proposed to predict co-receptor usage based on the viral genome sequences. A random forest based method is developed to predict co-receptor usage for new sequences using structures and sequences of "gp120".…”
Section: Biological Sequence Analysismentioning
confidence: 99%
“…A random forest based method is developed to predict co-receptor usage for new sequences using structures and sequences of "gp120". The good accuracy achieved in [16] made random forest a strong candidate for computational diagnosis of viral diseases.…”
Section: Biological Sequence Analysismentioning
confidence: 99%
“…Random Forests are increasingly popular in the biomedical community and enjoy good predictive success even against other machine learning algorithms in a wide variety of applications (Lunetta et al, 2004;Segal et al, 2004;Bureau et al 2005; Diaz-Uriarte and Alvarez de Andes 2006; Qi, Bar-Joseph and Klein-Seetharaman 2006; Xu et al, 2007;Archer and Kimes 2008;Pers et al 2009;Tuv et al, 2009;Dybowski, Heider and Hoffman 2010;Geneur et al, 2010). Random Forests have been used in HIV disease to examine phenotypic properties of the virus.…”
Section: Use In Biomedical Applicationsmentioning
confidence: 99%
“…Segal et al used Random Forests to examine the role of mutations in polymerase in HIV-1 to viral replication capacity . Random Forests have also been used to predict HIV-1 coreceptor usage from sequence data (Xu et al, 2007;Dybowski et al, 2010). Qi et al found that Random Forests had excellent predictive capabilities in the prediction of protein interaction compared to six other machine learning methods (Qi et al, 2006).…”
Section: Use In Biomedical Applicationsmentioning
confidence: 99%
“…To date, many bioinformatics methods for tropism prediction have been developed and tested. These bioinformatics predictors include support vector machines (SVM) [4,5], neural networks (NN) [6], decision trees [7], random forest [8], instance based reasoning [9], position specific scoring matrices (PSSM) [10], multiple linear regression [11], and the 11/25 rule [12]. However, these methods generally are developed by fitting a model onto the respective training set, and might not perform as well in independent or unseen datasets [13].…”
Section: Introductionmentioning
confidence: 99%